Collaborative research between education and medical on study of early childhood neuroscience - Jumiatmoko, Jumiatmoko (JECCE (Journal of Early Childhood Care and Education), 2020)
Student experiences information process causing particular behaviors while studying. Neuroscience is a study to understand behavior and mental process based on brain activity. In Indonesian, collaborative study between education and medicine on preschool-aged children’s neuroscience is still scarce. In fact that using this collaboration, some elements related to student’s behavior and information process can be seen. This paper spells out potential collaborative studies on neuroscience of preschool-aged children. This study is categorized into qualitative descriptive research. The data were collected through an in-depth interview with the head of education and research section of UNS Hospital and document study. The result of the study found a number of potential collaborative studies between UNS Hospital and ECE department of UNS, namely: 1) Assessing level of stress using Bio-neurofeedback; 2) Assessing Learning comfort using Electroencephalograph; 3) Assessing Interest and Aptitude using Electroencephalograph; and 4) Therapy on Gadget Addiction using Bio-neurofeedback. Those findings can be used as a basic for further research about neuroscience in early childhood.